Pengaruh Pengetahuan Keuangan, Sikap Keuangan dan Kepribadian Terhadap Manajemen Keuangan Pelaku UMKM di Kecamatan Saluputti - Sri Septiani Borotoding; Jemi Pabisangan Tahirs; Mince Batara (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The Influence of Financial Knowledge, Financial Attitudes and Personality on Financial Management of MSME Actors in Saluputti District". The purpose of the study was to determine the influence of financial knowledge, financial attitudes and personality on the financial management of MSME actors in Saluputti District. Data collection procedures used in this study are Observation, Literature Study and Questionnaire. By using data analysis techniques Validity Test, Reliability Test, Normality Test, Autocorrelation Test, Multicollinearity Test, Multiple linear Regression Test, t Test (partial), F Test (simultaneous) and Coefficient Determination Test (RÂ²). The results showed that financial knowledge, financial attitudes and personality simultaneously affect the financial management of MSME actors in Saluputti District